How AFTA are you? : a question to entrepreneurs who act locally but think globally - Bambang Sugeng (Gramedia Pustaka Utama, 2003)
Buku ini membahas mengenai afta,Perdagangan internasional(perdagangan bebas) sesama anggota asean